Structural health monitoring : an advanced signal processing perspective - Yan, Ruqiang; Chen, Xuefeng; Mukhopadhyay, Subhas Chandra (Springer, 2017)
This book highlights the latest advances and trends in advanced signal processing (such as wavelet theory, time-frequency analysis, empirical mode decomposition, compressive sensing and sparse representation, and stochastic resonance) for structural health monitoring (SHM). Its primary focus is on the utilization of advanced signal processing techniques to help monitor the health status of critical structures and machines encountered in our daily lives: wind turbines, gas turbines, machine tools, etc. As such, it offers a key reference guide for researchers, graduate students, and industry professionals who work in the field of SHM.
Keywords: Structural health monitoring.; elektronické knihy; electronic books